Designing Inclusive Early Childhood Experiences: Teacher Strategies with STEAM, Loose Parts, and PBL - Tanaya Qatrunada Rutriningtyas; Avanti Vera Risti Pramudyani; Dewi Eko Wati; Dwi Hastuti; Risanti Dhaniaputri; Irma Sukarelawan (IJECA (International Journal of Education and Curriculum Application), 2026)
The implementation of inclusive education in early childhood education settings requires innovative pedagogical strategies capable of accommodating children’s diverse learning needs while supporting their cognitive, socio-emotional, and metacognitive development. Previous research on STEAM and Problem-Based Learning (PBL) has primarily focused on creativity and cognitive achievement, with limited attention to how inclusivity is implemented through adaptive pedagogical practices in heterogeneous early childhood classrooms. Furthermore, the use of loose parts as flexible learning materials in inclusive STEAM–PBL learning remains underexplored. Therefore, this study aims to examine how inclusive pedagogical principles are implemented through the integration of STEAM, Problem-Based Learning (PBL), and loose parts-based activities in early childhood education. This study employed a qualitative case study approach. Data were collected through classroom observations, interviews, and documentation involving teachers and children during the learning process. The instruments used in this study included interview guidelines, classroom observation sheets, and documentation notes focusing on inclusive STEAM–PBL implementation. Findings indicate that the integration of STEAM–PBL and flexible materials supports inclusive learning through contextual problem-solving activities, interest-based collaboration, responsive scaffolding, dialogic presentations, and reflective practices. Children demonstrated increased participation, communication skills, collaborative engagement, self-confidence, persistence in problem-solving, and emerging metacognitive awareness. The use of flexible materials enabled children with diverse abilities to explore, represent, and communicate ideas according to their individual capacities. This study highlights the uniqueness of inclusive STEAM–PBL implementation through adaptive scaffolding, flexible learning materials, and reflective participation practices that support meaningful and participatory learning experiences in early childhood classrooms.